A Clinical Framework for Assessing Cannabis-Related Impairment Risk - MacCallum, Caroline A.; Lo, Lindsay A.; Pistawka, Carly A.; Christiansen, April; Boivin, Michael; Snider-Adler, Melissa (Frontiers in Psychiatry, 2022)
Clinicians play an important role in promoting safe and responsible medical cannabis use. One essential component to safe use is considering a patient’s risk of impairment. However, there remains a lack of practical guidance on how clinicians can evaluate this risk for medical cannabis patients. Here, a novel framework is presented for clinicians to assess and stratify cannabis-associated impairment risk. The proposed framework is intended to be used as a tool for healthcare providers to gain a more comprehensive review of a patient’s impairment-related factors. This framework can be used to assess impairment risk for patients currently using or considering medical cannabis. This assessment is recommended for all patients who perform safety-sensitive duties. Such assessments can inform patient-specific needs for support, education, and guidance, to ensure cannabis is used safely and responsibly.